THE PERFORMANCE OF LUPIN MEAL AS AN ALTERNATIVE TO FISHMEAL IN DIET OF JUVENILE PENAEUS MONODON UNDER POND CONDITIONS - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2003)
The present study was designed to investigate the performance of isonitrogenous practical diets containing different inclusion levels of dehulled lupin (Lupinus angustifolius) meal as an alternative for fish meal for juvenile Penaeus monodon (4.32 ± 0.57 g) reared in pens under pond conditions with a natural productivity. Five isonitrogenous experimental diets were formulated to contain 0, 10, 20, and 30% dehulled lupin (L. angustifolius) meal with a corresponding reduction in fish meal from 24 (0% replacement; D1 as control) to 18 (25% replacement; D2), 12 (50% replacement; D3) and 6% (75% replacement; D4) and a diet containing dehulled lupin (L. albus) meal formulated to be similar to D2 which was designated as D5 and used for comparison. Each treatment was tested in quadruplicate and arranged in a completely randomised design. In addition, a group of shrimp put in four pond pens was not fed, to estimate the contribution of pond natural production to shrimp growth. There was no significant effect (P>0.05) of different dietary treatments on mean individual weight gain (13.3-14.2 g), survival rate (88-93%) of shrimp, and feed conversion ratio (1.45-1.55). The presence of natural food in the pond was important to boost shrimp production and approximately 36-67% of growth of shrimp in the present study was supplied by natural food.  Under such conditions, dehulled lupin (L. angustifolius) meal can replace up to 75% of protein from fish meal at inclusion levels of up to 30% in isonitrogenous practical diets without any adverse effects on growth, survival, and feed conversion ratio of juvenile P. monodon. Although this study was performed using a pond pen model on a small scale, the results obtained have provided useful information on the potential of lupin based meals in a commercial semi-intensive shrimp farming.